Strategic Human Resource Management in SMEs: Exploring the Impact of HR Practices on Innovation and Performance in Chennai’s Export-Oriented Enterprises - K. S, Giridharan (International Journal of Psychosocial Rehabilitation, 2017)
In the dynamic landscape of modern business, Human Resource Management (HRM) emerges as a pivotal factor for organisations striving to maintain competitiveness amidst turbulent conditions. This study delves into the critical role of HRM practices in fostering innovation and enhancing organisational performance. Employing a comprehensive questionnaire based on a Likert scale, the research captures the perceptions of 126 managers and middle managers from export-oriented small and medium enterprises (SMEs) in Chennai, India. The study’s design aims to empirically test a model linking HRM practices to innovation and organisational outcomes. The findings reveal HRM’s significant impact on organisational performance and innovation. Notably, innovation is a crucial mediator that can potentially elevate organisational performance. However, a simultaneous testing process yields intriguing insights, indicating that innovation does not always translate into improved performance outcomes. This paradox highlights a critical gap in SMEs’ investment in human resources, underscoring the need for more strategic HRM approaches to drive innovation effectively. The study contributes to the existing literature by providing empirical evidence from a unique context, offering valuable implications for HRM practices in SMEs. It suggests a recalibration of HRM strategies to better harness the potential of human capital in driving innovation and achieving superior organisational performance.